Kualitas Perairan Pesisir Pantai Gili Trawangan Berdasarkan Fisika Kimia Perairan, Indeks Keanekaragaman Dan Spesies Indikator (Filum Mollusca) Sebagai Modul Ekologi Hewan - Usman, Usman; Azizi, Asrorul (Mataram University, 2024)
The purpose of this research is to know ecosystem changes of water in Gili Trawangan seashore with diversity index, physic chemical of water and species indicator of Mollusca. The result showed that diversity index is high with condition of physical chemical of water in standard tolerance level for Mollusca. Species indicator of Mollusca whose showed the water quality are yaitu Glycimeris pectunculus, Thais hippocastanum, Cypraea annulus, Harpa amouretta, Conus flavidus, Mitra proscissa and Strombus hirasei. Cypraea annulus, Turbo bruneus, Drupa grossularia, Mitra aurantia, dan Morulla marginalba. Littorinia pulchra dan Cerithium muscarum. Self instructional Module have developed is suitable in used by student.